Snakebite Management: The Need of Reassessment, International Relations, and Effective Economic Measures to Reduce the Considerable SBE Burden - Ramesh Kumar; Anurag S. Rathore (Springer, 2024)
Abstract The sole treatment for snakebite envenomation (SBE), the anti-snake venom (ASV), suffers from considerable drawbacks, including side effects and limited species specificity. Additionally, despite its existence for more than a century, uniform availability of good quality ASV does not yet exist. The present review describes the journey of a SBE victim and highlights the global crisis of SBE management. A detailed analysis of the current ASV market has also been presented along with the worldwide snake distribution. The current production of country specific licensed ASV throughout the globe along with their manufacturers has been examined at the snake species level. Furthermore, a detailed analysis of on-ground situation of SBE management in antivenom manufacturing countries has been done using the most recent literature. Additionally, the export and import of different ASVs have been discussed in terms of procurement policies of individual countries, their shortcomings, along with the possible solution at the species level. It is interesting to note that in most countries, the existence of ASV is really either neglected or overstated, implying that it is there but unsuitable for use, or that it is not present but can be obtained from other countries. This highlights the urgent need of significant reassessment and international collaborations not just for development and production, but also for procurement, distribution, availability, and awareness. A PROMISE (Practical ROutes for Managing Indigenous Snakebite Envenoming) approach has also been introduced, offering simple, economical, and easy to adopt steps to efficiently alleviate the worldwide SBE burden.